Acute fibrinous and organising pneumonia following lung transplantation is associated with severe allograft dysfunction and poor outcome: a case series. Issue 1 (December 2015) - Meyer, Keith; Bierach, Jennifer; Kanne, Jeffrey; Torrealba, Jose; Oliveira, Nilto
Abstract Acute fibrinous and organising pneumonia (AFOP) is a histopathologic variant of acute lung injury that has been associated with infection and inflammatory disorders and has been reported as a complication of lung transplantation. A retrospective chart review was performed for all patients transplanted at the University of Wisconsin Hospital and Clinics from January 1995 to December 2013 (n = 561). We identified 6 recipients whose clinical course was complicated by AFOP. All recipients were found to have AFOP on lung biopsy or at post-mortem examination, and 5 of the 6 patients suffered progressive allograft dysfunction that led to fatal outcome. Only 1 of the 6 patients stabilised with augmented immunosuppression and had subsequent improvement and stabilisation of allograft function. We could not clearly identify any specific cause of AFOP, such as drug toxicity or infection. Lung transplantation can be complicated by lung injury with an AFOP pattern on histopathologic examination of lung biopsy specimens. The presence of an AFOP pattern was associated with irreversible decline in lung function that was refractory to therapeutic interventions in 5 of our 6 cases and was associated with severe allograft dysfunction and death in these 5 individuals. AFOP should be considered as a potential diagnosis when lung transplant recipients develop progressive decline in lung function that is consistent with a clinical diagnosis of chronic lung allograft dysfunction.